2015
DOI: 10.1007/s00345-015-1589-1
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysreflexia and repeatability of cardiovascular changes during same session repeat urodynamic investigation in women with spinal cord injury

Abstract: In all women with NLUTD due to suprasacral SCI, we strongly recommend continuous cardiovascular monitoring during UDI and repeat measurements considering the high incidence of AD, the relevant risks involved with sudden hypertension and the poor repeatability of cardiovascular monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
(66 reference statements)
2
10
0
Order By: Relevance
“…For all other urodynamic parameters assessed, however, there were wide 95% limits of agreement for differences in the parameters, indicating poor repeatability. These findings are very similar to the results in patients with neurogenic LUTD [ 24 , 26 ] and highlight the importance of same session repeat UDI for clinical decision making.…”
Section: Discussionsupporting
confidence: 88%
“…For all other urodynamic parameters assessed, however, there were wide 95% limits of agreement for differences in the parameters, indicating poor repeatability. These findings are very similar to the results in patients with neurogenic LUTD [ 24 , 26 ] and highlight the importance of same session repeat UDI for clinical decision making.…”
Section: Discussionsupporting
confidence: 88%
“…The International Standards to document remaining Autonomic Function after Spinal Cord Injury (ISAFSCI) 17 recommends the diagnostic criteria for AD as a SBP increase of 420 mm Hg from baseline. Only two previous studies 14,15 used the same criteria; however, the study by Huang et al 14 did not clarify SBP, DBP and heart rate (HR) changes in the AD subgroup but only demonstrated a change in a combination of these CV parameters in all individuals with and without AD. Therefore, it is difficult to obtain data for evaluation of the severity of AD in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Linsenmeyer et al 12 found urodynamic examination to be an excellent way to detect whether individuals with SCI are prone to asymptomatic AD. Previous studies revealed incidences of AD during urodynamics, [11][12][13][14][15][16] but the diagnostic criteria varied among these studies. Some studies 12,13 used maximal SBP and DBP as criteria, whereas others 11,[14][15][16] just used SBP change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urodynamic investigation (UDI) is the gold standard to assess neurogenic lower urinary tract dysfunction (NLUTD) in patients with SCI [ 3 , 4 ], but it may induce AD [ 15 , 16 ]. Considering that it is currently not possible to know in advance which patient will experience AD during UDI and, of those with AD, to what extent the systolic blood pressure (SBP) will increase, we aimed to determine the overall incidence and predictors of AD during UDI.…”
Section: Introductionmentioning
confidence: 99%